Design and Construction of a Web-Based Inventory Management Information System Using the Safety Stock and Economic Order Quantity (EOQ) Methods - Adelia Sakinah Rahmah; Aninda Muliani Harahap (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2026)
Effective inventory management is essential to maintain stock availability and control inventory costs in distribution companies. PT Panasonic Gobel Indonesia, Medan Branch, still faces challenges due to non-integrated inventory recording, resulting in data inconsistencies, reporting delays, and difficulties in determining optimal order quantities. These issues increase the risk of stock shortages and excess inventory, highlighting the need for an integrated inventory management information system. This study aims to design and develop a web-based inventory management system using the Safety Stock and Economic Order Quantity (EOQ) methods. The research applies a Research and Development (R&D) approach with the Waterfall model, covering requirement analysis, system design, implementation, and testing stages. Data were collected through observation, interviews, and literature review. The system was developed using PHP with the Laravel framework, a MySQL database, and UML. Model validation was conducted by comparing system calculation results with manual theoretical calculations, while verification was performed through functional and user acceptance testing. The results show that the system can accurately record inventory data, monitor stock levels in real time, and automatically calculate EOQ and safety stock, thereby supporting efficient and optimal inventory control.Keywords - Economic Order Quantity (EOQ); Inventory Control; Inventory Management Information System; Safety Stock; Web-Based System